Development of Teaching Modules Using the Understanding by Design (UbD) Approach on Class X Chemical Bond Material - Rumahorbo, Nurli Yanti; Syafriani, Dewi; Agustina, Husna Sari (Pascasarjana, Mataram University, 2025)
This study aims to develop a teaching module based on the Understanding by Design (UbD) approach for 10th-grade students at SMA Negeri 4 Medan, with the specific objective of enhancing students’ conceptual understanding of chemical bonding. The research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects involved included 36 students of class X and one chemistry teacher. The instruments used in this study were expert validation sheets, teacher and student response questionnaires, and pretest-posttest assessments. Content and media validity were assessed by experts, resulting in validity percentages of 87% and 86%, respectively. Practicality was evaluated through teacher and student questionnaires, obtaining average scores of 93% and 93%, indicating the module is easy to use and well-received. Effectiveness was measured using the N-Gain formula, yielding a score of 73.58%, categorized as quite effective in improving students' understanding. Data were analyzed descriptively to determine the module's feasibility, practicality, and effectiveness. In conclusion, the UbD-based teaching module on chemical bonding is valid, practical, and effective in supporting students’ conceptual mastery of chemistry.